EARLY SENESCENCE1 Encodes a SCAR-LIKE PROTEIN2 That Affects Water Loss in Rice . Issue 2 (4th August 2015) - Rao, Yuchun; Yang, Yaolong; Xu, Jie; Li, Xiaojing; Leng, Yujia; Dai, Liping; Huang, Lichao; Shao, Guosheng; Ren, Deyong; Hu, Jiang; Guo, Longbiao; Pan, Jianwei; et al.
Abstract : An actin nucleation protein affects water loss by regulating stomatal density. Abstract: The global problem of drought threatens agricultural production and constrains the development of sustainable agricultural practices. In plants, excessive water loss causes drought stress and induces early senescence. In this study, we isolated a rice ( Oryza sativa ) mutant, designated as early senescence1 ( es1 ), which exhibits early leaf senescence. The es1-1 leaves undergo water loss at the seedling stage (as reflected by whitening of the leaf margin and wilting) and display early senescence at the three-leaf stage. We used map-based cloning to identify ES1, which encodes a SCAR-LIKE PROTEIN2, a component of the suppressor of cAMP receptor/Wiskott-Aldrich syndrome protein family verprolin-homologous complex involved in actin polymerization and function. The es1-1 mutants exhibited significantly higher stomatal density. This resulted in excessive water loss and accelerated water flow in es1-1, also enhancing the water absorption capacity of the roots and the water transport capacity of the stems as well as promoting the in vivo enrichment of metal ions cotransported with water. The expression of ES1 is higher in the leaves and leaf sheaths than in other tissues, consistent with its role in controlling water loss from leaves. GREEN FLUORESCENT PROTEIN-ES1 fusion proteins were ubiquitously distributed in the cytoplasm of plant cells. Collectively, our data suggest that ES1 is important for regulating water loss in rice.